Pengembangan Bahan Ajar Canva dalam Meningkatkan Semangat Belajar Peserta Didik pada Materi Hidangan Tradisional Indonesia - Sherly Yanuarendra Lova; Agus Ridwan Misbahuddin; Nur Badriyah; Rahmah Izza Safira; Revo Firmansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The advancement of digital technology has significantly transformed the education sector, including vocational learning, especially in the culinary field. However, based on initial observations at SMK YPM 2 Taman, the learning process still tends to rely on printed information sources such as books and Student Worksheets. This research aims to develop learning materials using Canva as a way to motivate students in their learning. The approach used in this study is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results from experts indicate that the developed learning materials are categorized as